Grass trimmer hand-arm vibration reduction using multi-axial vibration absorber. (September 2019) - Patil, Sushil S
In this investigation, the novel multi-axial vibration absorber is proposed to reduce the handle vibration of petrol engine grass trimmer. The proposed vibration absorber is designed using Dunkerley's equation and fabricated for testing. The experimental modal analysis of absorber is conducted to find resonance frequencies of the absorber and to validate the results obtained from equations. The experimental tests are carried on grass trimmer with absorber attached near handle location to find effectiveness of absorber in reducing hand-arm vibrations in the x, y and z directions. The result indicated that the total vibration value measured at the handle of grass trimmer is reduced by substantial level with the attachment of multi-axial vibration absorber.